2010
DOI: 10.1186/1756-6614-3-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid statuses on sodium/iodide symporter (NIS) gene expression in the extrathyroidal tissues in mice

Abstract: BackgroundIodide that is essential for thyroid hormone synthesis is actively transported into the thyroid follicular cells via sodium/iodide symporter (NIS) protein in vertebrates. It is well known that NIS expression in thyroid is regulated by the thyroid statuses mainly through thyroid stimulating hormone (TSH). Although NIS mRNA expressions in extrathyroidal tissues have been qualitatively reported, their regulation by thyroid statuses has not been well clarified.MethodsMale ICR mice aged four weeks were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…NIS plays key roles in transporting iodide to the gland [18]. Compared with the control group, the significant up-regulations of thyroidal NIS were observed in rats exposed to the mild ID and severe ID groups on GD19 and PN21 ( p < 0.05, Figure 5(B)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NIS plays key roles in transporting iodide to the gland [18]. Compared with the control group, the significant up-regulations of thyroidal NIS were observed in rats exposed to the mild ID and severe ID groups on GD19 and PN21 ( p < 0.05, Figure 5(B)).…”
Section: Resultsmentioning
confidence: 99%
“…TTF1 and PAX8 have been shown to regulate expression of thyroid-specific genes, such as Na + /I − symporter (NIS) [16,17]. As the thyroid iodide transporter, NIS plays a key role in iodide concentration that is an essential step in thyroid hormone (TH) synthesis [18]. Many kinds of thyroid disorders and ID are implicated in the alterations of the NIS gene [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The earlier work of Morgan et al (1968) suggested deposition of particle-associated I 2 in the nasopharyngeal tract as the major source of ingestion. As the sodium iodide transporter NIS has only rarely been demonstrated in lung tissue (Spitzweg et al 1998;Harun-Or-Rashid et al 2010), deposition may indeed be the most efficient pathway. However, more recent work by Harvey et al (2006;Harvey 2009) documented differences in gas uptake from that occurring as a result of particle deposition.…”
Section: Discussionmentioning
confidence: 96%
“…Doses adapted from studies in mice and rats were tested in a pilot-study (Hamidi et al, 2010;Harun-Or-Rashid et al, 2010). T3 and T4 were dissolved in 0.025% sodium hydroxide (0.1N) and tap water.…”
Section: Animals and Housingmentioning
confidence: 99%